Perancangan Sistem Informasi Akuntansi pada LAZIS Nurul Falah - Nuril Firdaus; Rohmawati Kusumaningtias (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
Effective and efficient zakat management requires the support of a good accounting information system. To improve the effectiveness and efficiency in ZIS management, an integrated information system is needed that helps in documenting ZIS collection and distribution activities and is easy to understand by system users. So that with the integrated accounting information system between divisions can improve the performance, accountability, and transparency of financial statements. This research aims to design an accounting information system at LAZIS Nurul Falah. The Research method uses a case study approach. The data in the study were obtained through interviews with LAZIS Nurul Falah administrators who are directly related to research objects, observations, and documentation. Design an accounting information system using context diagrams, data flow diagrams, and flowcharts. The design of an integrated accounting information system using a client-server can improve the performance of administrators in managing data, accessing data, and speeding up the financial management process. Keywords: Accounting Information System, Shari’ah Accounting, ZIS